An investigation of the effect of knowledge management aspects on organizational performance (case study: sepah bank in Ardebil province) - Sahebnazar, Daryoush; Dadfar, Ebrahim (International Journal of Scientific World, 2016)
The purpose of this study is to investigate knowledge management aspects on organizational performance of Sepah Bank in Ardebil Province. Research population includes all the employees, deputies and managers of Sepah Bank branches in Ardebil Province, which according to the table of Morgan, includes a total number of 169 subjects. Standard questionnaires were used for data collection. Research results showed that knowledge management aspects (knowledge storage, sharing and using) had a positive and significant effect on organizational performance variable and in general 80 percent of variance determines the organizational performance of Sepah Bank in Ardebil.